2014
DOI: 10.1016/j.bmcl.2014.07.079
|View full text |Cite
|
Sign up to set email alerts
|

Combination of chiral linkers with thiophenecarboximidamide heads to improve the selectivity of inhibitors of neuronal nitric oxide synthase

Abstract: To develop potent and selective nNOS inhibitors, a new series of double-headed molecules with chiral linkers that derive from natural amino acid derivatives have been designed and synthesized. The new structures integrate a thiophenecarboximidamide head with two types of chiral linkers, presenting easy synthesis and good inhibitory properties. Inhibitor (S)-9b exhibits a potency of 14.7 nM against nNOS and is 1134 and 322-fold more selective for nNOS over eNOS and iNOS, respectively. Crystal structures show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The inhibitor K S values, determined from an imidazole displacement assay are reported in µM for each inhibitor of bsNOS. Isolation and characterization of NOS inhibitors marked by α were previously reported in (Delker et al, 2010), β in (Huang et al, 2013), γ in (Huang et al, 2014), δ in (Holden et al, 2013), ξ in (Jing et al, 2014), π in (Holden et al, 2013), σ in (Huang et al, 2012), φ in (Huang et al, 2014), ψ (Holden et al, 2014), ϑ in (Cinelli et al, 2014), ϕ in (Kang et al, 2015, unpublished data), and θ reported here.…”
Section: Figuresupporting
confidence: 58%
See 1 more Smart Citation
“…The inhibitor K S values, determined from an imidazole displacement assay are reported in µM for each inhibitor of bsNOS. Isolation and characterization of NOS inhibitors marked by α were previously reported in (Delker et al, 2010), β in (Huang et al, 2013), γ in (Huang et al, 2014), δ in (Holden et al, 2013), ξ in (Jing et al, 2014), π in (Holden et al, 2013), σ in (Huang et al, 2012), φ in (Huang et al, 2014), ψ (Holden et al, 2014), ϑ in (Cinelli et al, 2014), ϕ in (Kang et al, 2015, unpublished data), and θ reported here.…”
Section: Figuresupporting
confidence: 58%
“…Since bacterial NOS-selective inhibitors had not yet been identified, we collected a diverse set of NOS inhibitors ( 1–25 ) from our previous NOS studies (Holden et al, 2013; Huang et al, 2012; Huang et al, 2014; Jing et al, 2014; Kang et al, 2014; Kohanski et al, 2007) as well as several newly synthesized molecules ( 26–36 ). The collected small molecule library ( 1–36 ) was composed of a chemically diverse set of aminopyridine derivatives (aminopyridinyl-2-ethyl, aminopyridinyl-2-benzyl, aminopyridinyl-2-phenyl), 7-azaindoles, thiopheneamidines, and 2-aminoquinolines.…”
Section: Methodsmentioning
confidence: 99%
“…Compounds 1 and 2 , having an amidine and a methylamine tail with a tetrahydroquinoline or indoline core, recently reported by other research groups, display good potency toward human nNOS. Although 3D structural information on these compounds with nNOS was not reported, our previous crystallographic experience indicates that the thiophene-carboximidamide moiety should occupy the substrate binding pocket over the heme and that the tetrahydroquinoline or indole core should share the binding site with the middle aromatic ring of 3 near the A and D ring propionates. The N-methyl-substituted alkylamine chains from the core should improve the selectivity and potency by interacting with residues peripheral to the active site.…”
Section: Introductionmentioning
confidence: 99%
“…The 3,4dihydroquinolin-2(1H)-one and 1,2,3,4-tetra-hydroquinolineinhibitors are derivatives of quinoline and contain a 6-substituted thiophene amidine group with excellent potency and selectivity for nNOS (IC 50 = 0.089) (Ramnauth et al, 2011;Yang et al, 2015). Furthermore, pyrrolidine derivatives containing one or two 2-amino-4-methylpyridine groups with a chiral pyrrolidine linker exhibited the best activity and potency of 9.7 nM (Jing et al, 2014). Several a-amino functionalized aminopyridine derivatives were designed to target to BH4 against nNOS, exhibiting a K i of 24 nM for nNOS, with 273 and 2822-fold selectivity against iNOS and eNOS, respectively (Kang et al, 2014).…”
Section: Nos Inhibitorsmentioning
confidence: 99%